Study of the diversity and colonization of arbuscular mycorrhizal fungi in Kolah'ghazy protected area, Isfahan Province - Nafiseh Sadat Moosavi; Ebrahim Sedaghati; Pezhman Khodaygan; Narges Hatami (علوم محیطی)
Introduction: Arbuscular mycorrhizal fungi (AMF-phylum Glomeromycota) are one of the most important beneficial soil microorganisms that form a mutualistic symbiotic relationship with the roots of more than 80% of terrestrial plant species. These fungi improve the mineral nutrients (especially phosphorus) and water uptake and enhance plant tolerance to various biotic and abiotic stresses such as pathogens, salinity, drought and heavy metals contamination. Hence, they play a key role in the establishment of plant communities in different ecosystems. The present study aimed to identify AMF species associated with different plants roots based on morphological characteristics, comparison of spore’s population and determine the percentage of root colonization in the Kolah'ghazi protected region in Isfahan Province.Material and methods: At first, 12 plants were selected from the predominant plants that are AMF hosts. The sampling was conducted from a depth of 5 to 30 cm in the rhizosphere of each plant and the soil and root samples were collected. Roots fragments were stained in lactoglycerol blue and the percentage of root colonization was calculated. AMF spores were extracted from each air-dried soil sample (300-500 g) by wet sieving and centrifugation in sugar solution methods. Also, spore populations were determined in a gram of soil with three replications. Then, the isolated spores were identified based on morphological characteristics such as color, shape, size, wall structure, hyphal attachment, etc.Results and discussion: Microscopic observations indicated that all the sampled plant roots were colonized by AMF. The percentage of AMF colonization ranged from 9-92% among plants species and the highest and lowest of it were observed in Thymus vulgaris and Alyssum homolocarpum plants, respectively. The highest spore density was in the rhizosphere of the Th. vulgaris and the lowest was related to Lepidium draba. The statistical analysis showed that there is a positive correlation between the percentage of mycorrhizal colonization and the number of spores in most plants. Based on morphological criteria, 12 species of AMF belonging to 8 genera Claroidoglomus (C. etunicatum and C. luteum), Funneliformis (F. caesaris and F. geosporum), Glomus (G. ambisporum), Rhizophagus (Rh. aggregatum and Rh. fasciculatus), Septoglomus (Se. africanum, Se. constrictum and Se. deserticola), Entrophospora (E. infrequens), Gigaspora (Gi. gigantea) and Scutellospora (Scutellospora sp.) were identified. Se. africanum is new for mycoflora from Iran and other identified species have previously been reported from different regions and crops.Conclusion: Due to the importance of AMF, identification and reproduction of these fungi for exploiting their potential in regenerate arid areas, especially protected areas, can be necessary. However, further research is needed to more accurately identify AM species.